Running, walking, and cross-country skiing: how to shape adolescents’ personalities through physical activity? - Gao, Yucheng; Che, Li; Li, Xiaotian (Frontiers in Psychology, 2024)
Adolescence is crucial for personality development, and sports play a significant role. This study investigates the impact of various sports on the personality traits of junior high and high school students in Shandong Province, focusing on neuroticism, extraversion, openness, agreeableness, and conscientiousness.Utilizing data from the "Database of Youth Health," we employed Seemingly Unrelated Regression (SUR) and Generalized Structural Equation Modeling (GSEM) to analyze the effects of physical activity on personality development.Findings reveal that walking significantly enhances openness and decreased neuroticism, while jogging/running substantially improves extraversion, agreeableness, and conscientiousness. Cross-country skiing, however,negatively impacts all assessed personality traits. In addition, the importance of gender differences in the relationship between physical activity and personality development was revealed. The results offer insights for promoting adolescent personality development through targeted sports activities.